Critical Thinking Analysis of Boarding and Regular Students in Physics Learning at MA NU Banat Kudus - Dewi Raokhil Iklima Fariyya; Sunyoto Eko Nugroho; Sulhadi (Universitas Negeri Semarang, 2025)
MA NU Banat Kudus has two educational programs: boarding and regular classes. These two programs differ, particularly in terms of independence; boarding school students live in school dormitories, which require them to be independent in many aspects of daily life. In addition, education in boarding schools is divided into two types, namely diniyah learning and regular learning, while regular students only have regular learning. Critical thinking is also an important aspect that must be considered. This study aims to analyze the differences in critical thinking skills and learning independence attitudes between boarding school and regular class students in physics learning at MA NU Banat Kudus. The method used in this study is a mixed methods with a triangulation design, combining a quantitative approach through tests and a qualitative approach through interviews. The study population consisted of grade XI students, divided into two groups: boarding and regular. Quantitative data analysis was carried out using the T test, while qualitative data were analyzed thematically. The results of the study showed that there was no significant difference in critical thinking between boarding school and regular students. Based on the t-test, a significant value of 0.67 was obtained, and the average results per aspect also showed no difference between boarding school and regular students. Meanwhile, the findings on student independence showed that boarding school students demonstrated better learning independence than regular students. This study recommends that schools develop more strategic planning for boarding programs to improve overall quality and implement active learning approaches, such as Problem-Based Learning, to enhance both critical thinking skills and learning independence among students in all types of schools.